About Ozolas, Philosophy Departments, about those Times. Bronislovas Genzelis interviewed by Algimantas Jankauskas - Jankauskas, Algimantas (Problemos, 2018)
[text in Lithuanian]Bronislovas Genzelis interviewed by Algimantas Jankauskas. Vilnius, March 3, 2018.Document: audiorecord (53 min.), privat collection of A. Jankauskas. Transcription: Lukas Strelnikovas.
Keywords: none